Dampak Turnover Pegawai Terhadap Kinerja Organisasi Perguruan Tinggi di Jawa Tengah - Miftahurrohman Miftahurrohman; Munifah Munifah (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
The aim of this research is to find out what factors cause turnover and also to find out the impacts of high turnover. The research approach uses descriptive research with a sample size of 138, data analysis techniques use quantitative and qualitative analysis techniques. The research results show that the factors that influence employee turnover are job satisfaction, job demands and opportunities, work environment, commitment and leadership. High turnover will have impacts including the loss of several highly experienced and skilled employees, causing a decrease in employee productivity and a decrease in the quality of services provided and ultimately will have an impact on decreasing organizational performance and hampering the achievement of organizational goals.